Traditions and current trends of china's vocal and choir school development - Khay Lin (Academy of Cognitive and Natural Sciences, 2006)
The article reveals ancient traditions and significance of singing activities in China. The modem tendencies оf development of Chinese vocal-choral schools are characterized as well.